Fate and bioavailability of four conazole fungicides in twelve different arable soils - Effects of soil and pesticide properties - Šudoma, Marek; Neuwirthová, Natália; Hvězdová, Martina; Svobodová, Markéta; Bílková, Zuzana; Scherr, Kerstin E; Hofman, Jakub (Chemosphere, 2019)
The objective of this study is to characterize changes in the fate, behaviour and bioavailability of four conazole fungicides - CFs (prochloraz - PRO, tebuconazole - TEB, epoxiconazole - EPO, flusilazole - FLU) in 12 diverse agricultural soils in complex microcosm systems consisting of agriculturally-used fluvisols, plants (Lactuca sativa), earthworms (Eisenia fetida) and passive samplers (SPME, Empore™ discs, silicone rubber). Due to great variability of the data and other methodological problems, the in-matrix passive samplers failed to be indicators of pore-water concentration and (bio)availability/(bio)accessibility of CFs. A dissipation of all CFs followed the first order kinetics (usually after initial lag phase) with large span of resulting half-lives (7-670 d) depending on soils and compounds. In many soils, the model revealed the ending plateau, which indicates the non-degradable or slowly-degradable residues. The half-lives and the residues were generally higher for EPO and FLU, than for PRO and TEB. Greater but slower total dissipation of CFs was observed in soils with higher percentage of organic matter. Earthworm concentrations were highest at first sampling time (14 days) and considerably decreased afterwards often resulting in PRO concentration below LOQ. Earthworm uptake was influenced by amount of organic matter and soil texture. Accumulation to lettuce roots was generally higher than to leaves and differed greatly among CFs. Concentration shoot to root ratios were generally the lowest for FLU (0.04) and highest for TEB (0.37). PRO was not detected in lettuce leaves during experiment. The study brings new results on fate and bioavailability of CFs in soils.
Keywords: Soil microcosm; Animals; Plant; salát (hlávkový); Soil Pollutants; Biological Availability; Oligochaeta; zemědělství; triazoly; látky znečišťující půdu; biologická dostupnost; Conazole fungicides; Degradation; Earthworm; Triazoles; Bioaccumulation; Fungicides, Industrial; Lactuca; zvířata; Soil; průmyslové fungicidy; půda; Agriculture